Effects of head position on back squat power performance - Christopher George Offley; Jeremy Moody; Joseph Esformes; Paul Byrne (Asociación Española de Ciencias del Deporte, 2021)
The effect of head positioning is often not accounted for when optimising performance in the back squat exercise. The primary aim of the study was to identify the most advantageous head position for peak power (PP), peak velocity (PV) and peak force (PF) performance in the back squat exercise. A secondary aim was to identify the most favourable head position. Twenty male rugby union players performed 1x3 repetitions at 75% one repetition maximum (1RM) to determine their preferred pre-intervention head position, followed by 1x3 at 75% 1RM in a flexed (FP), extended (EP) and neutral (NP) neck position, performed in a counterbalanced and randomised order. PP, PV, PF and comfort level (CL) were measured during each repetition. FP resulted in significantly higher PP (3147.50 ± 464.70 W; p<0.05) compared to EP (2730 ± 427.83 W) and NP (2912.95 ± 441.16 W). However, NP resulted in significantly greater CL than FP and EP (3.65 ± 0.59; p<0.05). Therefore, when performing the back squat at 75% 1RM, the FP can be adopted to optimise power performance if there is no pain and no detriment to movement kinematics.